China‘s Global Vision for Ecological Civilization Theoretical Construction and Practical Research on Building Ecological Civilization - Pan, Jiahua (Springer Nature Singapore : Imprint: Springer, 2021)
XI, 173 p. 2 illus., 1 illus. in color.